ANALISIS FAKTOR – FAKTOR YANG MENDORONG PERGANTIAN KANTOR AKUNTAN PUBLIK (KAP) Studi Pada Perusahaan Publik di Indonesia Tahun 2007 - 2012 - Arinta, Khasaras Dara; Adiwibowo, Santosa (Diponegoro Journal of Accounting, 2013)
This research aims to know empirical evidence as for factors influencing  auditor switching on company listed in Indonesia Stock Exchange. The factors to be analysised in this research in  audit fees (FEE), audit opinion (OPINI), firm size (KAP), client size (LnTa), management turnover (CHM) and financial distress (DER).The data being used is from company which is listed in “Bursa Efek Indonesia” (BEI) in 2007 – 2012 period. Total sample in this research 510 companies using purposive sampling. Examinition of hypothesis conducted by using logistic regression.Results of this research are that auditor size and client size has significant effect on auditor switching. While other factors like audit opinion, client size, management turnover and financial distress do not have significant effect on auditor switching.